The Tripartite Structure of Sustainability: a new educational approach to bridge the gap to wise and sustainable action - Meyer, Barbara E. (Frontiers in Education, 2023)
This article argues that the success of today’s education has to be measured by the number of people who act wisely in crisis-ridden times, which also translates into acting sustainably. Research shows that education leads to knowledge, values, attitudes, judgments, and intentions to live sustainably, but people do not act on them. I refer to the gap between inner movements and actual behavior as the "inner-outer gap" and ask: "Is there an evident model or concept that educators can use to help their students bridge this gap?” The exploratory literature review shows that the answer is no. There are many helpful models in research on morality, moral automaticity, domain theory, and there are empirical models to explain sustainable action, but there is no single model that does the trick of showing how to bridge the gap. This raises the second question, if an amalgamation of different models might be helpful. In the discussion I used a segmentation method to fuse different theories and present a new approach within this article: The Tripartite Structure of Sustainability. It describes that actions are carried out under the impression of one of three foci, each of which can have a stable, situational or an automated quality. Empirical research leads to the hypothesis that a self-focus reinforces the gap, a self-transcendent focus bridges it, and a social focus may do both, depending on the social environment. If the hypothesis proves true, the model could help educators decide what to focus on to promote wise behavior in our unsettle world.